Social Semiotic of Covid-19 Health Protocol: Systemic Functional Linguistics - I Ketut Suardana (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Background: Covid-19 is viewed as multimodality, it can be analyzed from many lives aspects point of view. This research analyzed Covid-19 health protocol from Systemic Functional Linguistics perspective. The data were taken in Denpasar from 2020 to 2021 in non-verbal language such as; using masker, using face shield, washing hand, working from home, and keeping distance. The theory used for this research is the theory of Systemic Functional Linguistics proposed by Halliday and Ruqaiya, related to social semiotic. In addition, there are two theories used to support the analysis, namely theory of sign proposed by Peirce and theory of maxim proposed by Grice.Methodology: The research employed qualitative research, phenomenology research. The researcher observed communities’ health protocols to find the data. The data were taken in Denpasar from 2020 to 2021 in connotative references by non-verbal language.Findings: The result of the research is presented in description. The research suggested that (i) Using masker is interpreted that we must control what we speak. What we speak must have correlation with Grice’s maxims theory. (ii) Using face shield is associated with thinking positively. We must think positively in every phenomenon. (iii) Washing hands means that we must use our hand based on the right function. (iv) Working from home is interpreted that we have to improve our selves through learning and studying. (v) Keeping distance is associated that we have to focus on what we want to achieve.Conclusion: The ideology of social behaviors represents that we have to follow the moral values embedded in such non-verbal language to get harmony. The findings of the texts are (i) the text belongs to motivation to get harmonies in the life, (ii) the text teaches us how to get success, and (iii) the reference of the signs is categorized rheme. The text is categorized as procedural text. Originality: The research is hoped to be able to give the meaning of health protocol performance by social semiotics approach.